INFLUENCE OF INSPIRATIONAL MOTIVATION ON THE PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Nyakomitta, Kennedy O.; Namusonge, Prof. Gregory S.; Amuhaya, Prof. Iravo Mike (Journal of Human Resource and Leadership, 2018)
Purpose: The purpose of this study was to establish the influence of inspirational motivation on the performance of commercial banks in Kenya. Methodology: The study employed mixed research design, which included both qualitative and quantitative methods. The study target population was all tier 1 commercial banks in Kenya. According to CBK, there are seven tier 1 banks namely; Kenya Commercial Bank, Equity Bank, Cooperative Bank, Standard Chartered Bank, Barclays Bank, Diamond Trust Bank and Commercial Bank of Africa. The choice of tier 1 banks as the unit of observation was justifiable since they contribute to over 50% of all banking employees, and therefore, they form a good ground for random stratification. The study covered a target population of 24,244 employees working in the seven banks. A sample size of 384 was selected from all the seven banks using stratified random sampling. Primary data was collected using well-structured questionnaires. Multiple linear regression model was used to estimate the coefficients using statistical package for the social sciences (SPSS version 23). Descriptive and inferential analyses were used to analyze the data. Results: Based on the findings, the study concluded that inspirational motivation affects the performance of commercial banks in Kenya. This can be explained by the regression results which showed that the effect was positive and also showed the magnitude by which inspirational motivation influenced the performance of commercial banks. The regression results showed that inspirational motivation influenced the performance of banks by 0.779 units. Unique contribution to theory, practice and policy: The study recommended that the banks' leadership should encourage managers and employees to apply behaviors associated with inspirational motivation to improve the performance of the organization. These behaviors include clarity with which they communicate the organization's vision, inspiration motivation and encouraging team spirit. Managers can additionally reinforce inspirational motivation behaviors among their followers because they improve the effectiveness of a leader in realizing better performance results.